Tread-Braked Wheels: Review and Recent Findings - Gianluca Megna; Andrea Bracciali (Machines)
Tread braking is still extensively used on freight wagons due to lower purchasing and maintenance costs compared to disk braking. Cast iron brake blocks were replaced by composite materials (organic or sintered) that result in a lower wheel roughness, reducing rolling noise. Unfortunately, composite brake blocks have a lower thermal conductivity, negatively affecting the wheel mechanical behavior as the braking energy is almost entirely dissipated by the wheels, which are therefore subjected to higher temperatures. Mechanical properties of the wheel material, such as yield stress and Rolling Contact Fatigue (RCF) behavior, markedly decrease with temperature, resulting in higher wear rates and wheel tread damage. Contacted to analyze defects not clearly defined in the current regulations used for maintenance and inspections, the authors surveyed the literature and the technical documentation about tread-braked wheels. The paper provides an updated view about the state-of-the-art of the research on thermomechanical behavior of railway wheels and discusses the implication of the increased thermal stresses generated by composite brake blocks.